umor necrosis factor production in acute malaria (Colombia Medica, 1989)
The tumor necrosis factor (TNF) is a cytokine released by activated macrophages. It may play an important role in either the protection or pathology of malaria. Mononuclear cells of 40 infected patients with Plasmodium falciparum or P. vivax were evaluated for the spontaneous release of TNF in vitro. High levels of the factor were observed in 50% of these supernatants. No correlation was found between TNF values and parasitemia, blood chemistry, or fibrinogen levels.